Novel Highly Efficient Organophotocatalysts: Truxene–Acridine‐1, 8‐diones as Photoinitiators of Polymerization. Issue 19 (9th August 2013) - Tehfe, Mohamad‐Ali; Dumur, Frédéric; Contal, Emmanuel; Graff, Bernadette; Gigmes, Didier; Fouassier, Jean‐Pierre; Lalevée, Jacques
<x xml:space="preserve">Abstract</x> Truxene–acridine‐1, 8‐dione derivatives (Tr_AD) are proposed as new photoinitiators of polymerization under very soft irradiation (by a household halogen lamp), as well as laser‐diode exposure at 405 nm. They exhibit a strong absorption around 380 nm. The Tr_AD/diphenyl iodonium salt/9‐vinylcarbazole combination is able to promote the ring‐opening polymerization of an epoxide, whereas the Tr_AD/alkyl halide/amine system is very efficient in initiating the radical photopolymerization of an acrylate. Excellent polymerization profiles are obtained. Acrylate/epoxide blends are also easily polymerized. These Tr_ADs in the three‐component systems behave as photocatalysts according to oxidative cycles. The mechanisms are discussed for the different multicomponent initiating systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>